Computer-Intensive Methods for Testing Hypothesis: An Introduction. - McKeown, James C.; Moriarty, Shane R. (The Accounting Review, 1990)
Abstract Reviews the book `Computer-Intensive Methods for Testing Hypothesis: An Introduction,' by Eric W. Noreen.